2017
DOI: 10.1016/j.ijheatmasstransfer.2016.09.051
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the effects of nanoparticles deposition on characteristics of the heating surface and ON pool boiling of water

Abstract: Nanofluid pool boiling can modify the morphology of the heating surface and the physical properties of the base fluids, interfering directly on the vapor bubbles dynamics and on the heat transfer mechanisms. This paper concerns an experimental investigation of the effects of surface roughness and nanoparticle deposition on the contact angle, surface wettability and pool boiling heat transfer coefficient (HTC). Experiments were carried out using copper surfaces with different roughnesses, and deionized water as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 27 publications
4
46
0
Order By: Relevance
“…The curve fittings were obtained with R-square higher than 0.99. The assumption of negligible heat losses in the radial direction done by Kiyomura et al [35] seemed suitable for this work, otherwise a linear profile would not fit the experimental data. Besides, the comparison between the imposed heat flux based on the electrical current and voltage measurements, and the heat flux estimated from the linear profile indicated heat losses always lower than 12%, as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The curve fittings were obtained with R-square higher than 0.99. The assumption of negligible heat losses in the radial direction done by Kiyomura et al [35] seemed suitable for this work, otherwise a linear profile would not fit the experimental data. Besides, the comparison between the imposed heat flux based on the electrical current and voltage measurements, and the heat flux estimated from the linear profile indicated heat losses always lower than 12%, as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The apparatus used to measure the static contact angle consists of an aluminum plate where the test surface is fixed, a camera, a green LED light source and a light diffuser. The pictures were analyzed using image post processing software to shape the deionized water droplet, as detailed in Kiyomura et al [35] and Netto et al [37].…”
Section: Surface Characterizationmentioning
confidence: 99%
“…Kiyomura et al [16] studied the effects of nanoparticles deposition on characteristics of the heating surface of pool boiling of water, and in their study, they tested several types of surfaces: smooth surface (SS), rough surface (RS), smooth surface-low concentration (SS-LC), smooth surface-high concentration (SS-HC), rough surface-high concentration (RS-HC), and rough surface-low concentration (SS-LC). Results showed that both surfaces (RS-HC and RS-LC) presented deteriorated HTC when compared with the surface without deposition.…”
Section: Recent Studies On Pool Boiling Of Nanofluidsmentioning
confidence: 99%
“…As the performance of the aforementioned technologies strongly depend on boiling heat transfer performance, the issue of increasing boiling heat transfer coefficients becomes of the great importance. Plenty of techniques to enhance the boiling heat transfer coefficients of water have been proposed, mainly concerning heat transfer surface modification [8][9][10][11] or the addition of nanoparticles (so called nanofluids) [12,13]. Jones et al [14] performed experimental studies of the effects of surface roughness on nucleate pool boiling heat transfer.…”
Section: Introductionmentioning
confidence: 99%